Heterogeneous Electrocatalyst with Molecular Cobalt Ions Serving as the Center of Active Sites - Wang, Jiong (2017)
Molecular Co2+ ions were grafted onto doped graphene in a coordination environment, resulting in the formation of molecularly well-defined, highly active electrocatalytic sites at a heterogeneous interface for the oxygen evolution reaction (OER). The S dopants of graphene are suggested to be one of the binding sites and to be responsible for improving the intrinsic activity of the Co sites. The turnover frequency of such Co sites is greater than that of many Co-based nanostructures and IrO2 catalysts. Through a series of carefully designed experiments, the pathway for the evolution of the Co cation-based molecular catalyst for the OER was further demonstrated on such a single Co-ion site for the first time. The Co2+ ions were successively oxidized to Co3+ and Co4+ states prior to the OER. The sequential oxidation was coupled with the transfer of different numbers of protons/hydroxides and generated an active Co4+═O fragment. A side-on hydroperoxo ligand of the Co4+ site is proposed as a key intermediate for the formation of dioxygen.